Development of self-assembled multi-arm polyrotaxanes nanocarriers for systemic plasmid delivery in vivo. (February 2019) - Ji, Ying; Liu, Xiangsheng; Huang, Max; Jiang, Jinhong; Liao, Yu-Pei; Liu, Qi; Chang, Chong Hyun; Liao, Han; Lu, Jianqin; Wang, Xiang; Spencer, Melissa J.; Meng, Huan
Abstract: Polyrotaxane (PRX) is a promising supramolecular carrier for gene delivery. Classic PRX exhibits a linear structure in which the amine-functionalized α-cyclodextrin (CD) is threaded along the entire polyethylene glycol (PEG) backbone. While promising in vitro, the absence of free PEG moieties after CD threading compromised the in vivo implementation, due to the unfavorable pharmacokinetics (PK) and biodistribution profile. Herein, we developed a multi-arm PRX nanocarrier platform, which has been designed for protective nucleic acid encapsulation, augmented biodistribution and PK, and suitable for intravenous (IV) administration. A key design was to introduce cationic CD rings onto a multi-arm PEG backbone in a spatially selective fashion. The optimal structural design was obtained through iterative rounds of experimentation to determine the appropriate type and density of cationic charge on CD ring, the degree of PEGylation, the size and structure of polymer backbone, etc . This allowed us to effectively deliver large size reporter and therapeutic plasmids in cancer mouse models. Post IV injection, we demonstrated that our multi-arm polymer design significantly enhanced circulatory half-life and PK profile compared to the linear PRX. We continued to use the multi-arm PRX to formulate a therapeutic plasmid encoding an immunomodulatory cytokine, IL-12. When tested in a colon cancer syngeneic mouse model with same background, the IL-12 plasmid was protected by the multi-arm PRX and delivered through the tail vein to the tumor site, leading to a significant tumor inhibition effect. Moreover, our delivery system was devoid of major systemic toxicity.